Pengaruh Kapasitas Cavitation Air Flotation Terhadap Penurunan Total Suspended Solid Berdasarkan Baku Mutu Air Limbah di PT. X - Yudhi Chandra Dwiaji; Tio, Monika (Indonesian Society of Applied Science, 2025)
Effluent Treatment Plant (ETP) is an environmentally based regional waste treatment system that aims to treat liquid waste so that it can produce waste that meets quality standards. Liquid waste that cannot be treated properly can result in environmental pollution. The research methodology used is a method of observation study by direct observation including the processing process in the ETP plant, the data collected is calculated based on the parameters of liquid waste before and after processing. From the data, there are several days that show that only 80% of waste can be treated on ETP from the total waste sent from the production plant. This has an impact on the quality of TSS (Total Suspended Solid) parameters treated at CAF experiencing outspec of 20.79% of the operational standards of TSS parameters in PT X. Based on the results of research found that CAF (Cavitation Air Flotation) capacity is less maximal when the flowrate of waste to be treated is high so that the treatment capacity in ETP cannot keep up with the amount of waste sent from the production plant. This can cause the level in the accident pond and equalization pond high and eventually result in wastewater overflowing into the environment so from this analysis process is obtained the proposed improvement of the process to improve the performance of IPAL is to add CAF to the pre-treatment process.